Foreign Investment Law : how customary is custom? - Orrego Vicuña, Francisco (Estudios Internacionales, 2005)
Comments made at the Panel on the New Regime for Foreign Direct Investment, American Society of International Law 2005 annual meeting, Washington D.C., March 31, 2005